2014
DOI: 10.1038/srep03650
|View full text |Cite
|
Sign up to set email alerts
|

Indigo carmine: An organic crystal as a positive-electrode material for rechargeable sodium batteries

Abstract: Using sodium, instead of lithium, in rechargeable batteries is a way to circumvent the lithium's resource problem. The challenge is to find an electrode material that can reversibly undergo redox reactions in a sodium-electrolyte at the desired electrochemical potential. We proved that indigo carmine (IC, 5,5′-indigodisulfonic acid sodium salt) can work as a positive-electrode material in not only a lithium-, but also a sodium-electrolyte. The discharge capacity of the IC-electrode was ~100 mAh g−1 with a good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 39 publications
7
101
0
Order By: Relevance
“…The potential profiles of the DMBQ electrode during the first cycle are shown in Figure 5. The first discharge curves show two potential plateaus that we often observe for quinone-based electrodes in Li, 8 Na 20 and Mg 7 systems. For all of these solutions, the plateaus are located at around 0.8 and 0.4 V vs. Mg quasi , which are about 2 V lower than those in the Li system.…”
Section: Resultsmentioning
confidence: 54%
“…The potential profiles of the DMBQ electrode during the first cycle are shown in Figure 5. The first discharge curves show two potential plateaus that we often observe for quinone-based electrodes in Li, 8 Na 20 and Mg 7 systems. For all of these solutions, the plateaus are located at around 0.8 and 0.4 V vs. Mg quasi , which are about 2 V lower than those in the Li system.…”
Section: Resultsmentioning
confidence: 54%
“…The limited cyclability could be attributable to the non-optimized Na electrolytes of the cell and the large strain of the electrode materials during the insertion of large sodium ions, which may induce the isolation of the active materials from the electrodes. While further studies are required, the sodium-organic battery system is promising for sustainable energy storage systems, since it is based on abundant sodium elements on earth and does not contain transition metals [38][39][40] . The utilization of diazabutadiene redox cycling should provide potential opportunities for sodium-organic battery systems.…”
Section: Resultsmentioning
confidence: 99%
“…2e4 Recently, indigos and functionalized indigos were applied for optoelectronic devices, such as field effect transistors, 5e7 solar cells, 8,9 sensors, 10,11 and electrodes for ion batteries. 12,13 In particular, Pitayatanakul et al, reported on the halogen or phenyl group functionalized indigos for organic semiconductors. In this series of compounds, the indigos showed a herring-bone like structure for the halogen substitution derivatives, whereas a brickwork arrangement of the crystal structure was observed in the case of phenyl-derivatives because of pep interactions arising from the functionalization substitution at 5-position.…”
Section: Introductionmentioning
confidence: 98%